1991
DOI: 10.1007/bf02457636
|View full text |Cite
|
Sign up to set email alerts
|

Polar effects of concanavalin A on the cortical cytoskeleton of a molluscan egg (Nassarius reticulatus, Gastropoda)

Abstract: The organization of the surface of fertilizedNassarius reticulatus eggs was probed by investigating the effects of treatment with concanavalin A (Con A). This lectin causes abnormal polar lobe formation as well as inhibition of cleavage. At low concentrations of Con A (0.3-1.0 μg/ml) the polar lobe constriction becomes considerably elongated, whereas at higher concentrations (2.5-50 μ/ml) the position of the constriction undergoes an extreme shift towards the animal pole. In the latter case, the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies have d e m o n s t r a t e d that the vegetal m e m b r a n e o f the Nassarius egg is e n d o w e d with special properties, such as increased lateral m o b i l i t y o f m e m b r a n e lipids, as well as a higher density o f i n t r a m e m b r a n e particles (Speksnijder et al 1985a, b). In addition, in our accomp a n y i n g p a p e r (Speksnijder et al 1991), we concluded that the p a r t i c u l a r effects o f C o n A on p o l a r lobe formation are p r o b a b l y due to binding o f C o n A to sites at the vegetal pole. Thus, the cell lineage-specific effects of Con A on cleavage could be explained by inheritance of this vegetal membrane by the CD-blastomere.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Previous studies have d e m o n s t r a t e d that the vegetal m e m b r a n e o f the Nassarius egg is e n d o w e d with special properties, such as increased lateral m o b i l i t y o f m e m b r a n e lipids, as well as a higher density o f i n t r a m e m b r a n e particles (Speksnijder et al 1985a, b). In addition, in our accomp a n y i n g p a p e r (Speksnijder et al 1991), we concluded that the p a r t i c u l a r effects o f C o n A on p o l a r lobe formation are p r o b a b l y due to binding o f C o n A to sites at the vegetal pole. Thus, the cell lineage-specific effects of Con A on cleavage could be explained by inheritance of this vegetal membrane by the CD-blastomere.…”
Section: Discussionmentioning
confidence: 81%
“…It seems, therefore, that the egg cortex is not capable of responding fully to this furrowing signal and that the assembly of a contractile ring, or its contraction, is inhibited by the action of Con A. Our accompanying paper indeed shows that Con A-binding greatly affects the organization of filamentous (F)-actin in the egg cortex (Speksnijder et al 1991), which we suggest may be caused by altered levels of intracellular calcium ions.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations